Roles of Pannexin-1 Channels in Inflammatory Response through the TLRs/NF-Kappa B Signaling Pathway Following Experimental Subarachnoid Hemorrhage in Rats - Wu, Ling-Yun; Ye, Zhen-Nan; Zhou, Chen-Hui; Wang, Chun-Xi; Xie, Guang-Bin; Zhang, Xiang-Sheng; Gao, Yong-Yue; Zhang, Zi-Huan; Zhou, Meng-Liang; Zhuang, Zong; Liu, Jing-Peng; Hang, Chun-Hua; et al. (Frontiers in Molecular Neuroscience, 2017)
Background Accumulating evidence suggests that neuroinflammation plays a critical role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). Pannexin-1 channels, as a member of gap junction proteins located on the plasma membrane, releases ATP, ions, second messengers, neurotransmitters, and molecules up to 1 kD into the extracellular space, when activated. Previous studies identified that the opening of Pannexin-1 channels is essential for cellular migration, apoptosis and especially inflammation, but its effects on inflammatory response in SAH model have not been explored yet. Methods Adult male SD rats were divided into six groups: sham group (n=20), SAH group (n=20), SAH + LV-Scramble-ShRNA group (n=20), SAH + LV-ShRNA-Panx1 group (n=20), SAH + LV-NC group (n=20) and SAH + LV-Panx1-EGFP group (n=20). The rat SAH model was induced by injection of 0.3 ml fresh arterial, nonheparinized blood into the prechiasmatic cistern in 20 s. In SAH + LV-ShRNA-Panx1 group and SAH + LV-Panx1-EGFP group, lentivirus was administered via intracerebroventricular injection (i.c.v.) at 72h before the induction of SAH. The Quantitative real-time polymerase chain reaction, electrophoretic mobility shift assay, enzyme-linked immunosorbent assay, immunofluorescence staining and western blotting were performed to explore the potential interactive mechanism between Pannexin-1 channels and TLR2/TLR4/NF-κB-mediated signaling pathway. Cognitive and memory changes were investigated by the Morris water maze test. Results Administration with LV-ShRNA-Panx1 markedly decreased the expression levels of TLR2/4/NF-κB pathway-related agents in the brain cortex and significantly ameliorated neurological cognitive and memory deficits in this SAH model. On the contrary, administration of LV-Panx1-EGFP elevated the expressions of TLR2/4/NF-κB pathway-related agents, which correlated with augmented neuronal apoptosis. Conclusion Pannexin-1 channels may contribute to inflammatory response and neurobehavioral dysfunction through the TLR2/TLR4/NF-κB-mediated pathway signaling after SAH, suggesting a potential role of Pannexin-1 channels could be a potential therapeutic target for the treatment of SAH.